2003
DOI: 10.1007/s00264-003-0456-7
|View full text |Cite
|
Sign up to set email alerts
|

Foot pump prophylaxis for deep venous thrombosis?rate of effective usage following knee and hip arthroplasty

Abstract: We recorded the usage of foot pumps during the post-operative period in 29 patients undergoing knee or hip arthroplasty and made 621 recordings. Effective utilisation of foot pumps was seen in 37.2% of cases. There was a gradual reduction in correct utilisation with each day that passed post-operatively (day 1, 60.4%; day 2, 48.8%; day 3, 28.8%; day 4, 21.4%; day 5, 23%). This gradual reduction was statistically significant (P=0.001) and mainly occurred between the second and third postoperative days. Effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 12 publications
0
24
1
2
Order By: Relevance
“…Following TKR, the effectiveness of foot pumps is less certain, with some studies reporting a benefit and others not [3,18]. In some of these studies GCS were not used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following TKR, the effectiveness of foot pumps is less certain, with some studies reporting a benefit and others not [3,18]. In some of these studies GCS were not used.…”
Section: Discussionmentioning
confidence: 99%
“…Compliance and tolerance have been reported to be a problem with the use of pneumatic compression systems [3,12]. Pitto et al reported a termination rate of 13.8% (16/116 patients) [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same study reported that only five out of the 244 patients required antenatal thromboprophylaxis, however, two of these were not assessed appropriately. There is evidence that correct use and compliance with of foot pumps is also an issue, with appropriate use as low as 36% (Charalambous et al, 2003).…”
Section: Pharmacological Thromboprophylaxismentioning
confidence: 99%
“…(A) (8) Em cirurgias ortopédicas, também há alguns estudos com as bombas pneumá-ticas para pés. (9) Os métodos mecânicos também podem ser usados em associação a medidas farmacológicas em pacientes com alto risco de TEV. (A) (10) Cirurgias neurológicas maiores requerem profilaxia para TEV.…”
Section: Tromboprofilaxia Primáriaunclassified